UNSUR ESTETIKA DALAM MANGA GEKKAN SHOUJO NOZAKI-KUN DAN RELEVANSINYA DENGAN MATERI MENGGAMBAR EKSPRESIF KELAS V SD/MI - Islami, Dani; Puspidalia, Yuentie Sova (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
Art is a medium for creativity. One of the most common art activities is expressive drawing. It involves the inner elements of the creator. Expressive drawing has been introduced in elementary school, but it is only explored in grade 5. However, in practice, teachers often adapt the conventional process by observing objects around them. In relation to this, there is one medium that can be used as a source of learning expressive drawing, namely Manga. This is because many elementary school students are familiar with and interested in the world of animanga. The purpose of this study is to describe the aesthetic elements and explain their relevance in Manga Gekkan Shoujo Nozaki-kun, with the content of expressive drawing material in the 5th grade Fine Arts book. The research used a qualitative method with literature review. Data were collected using the methods of listening, note-taking, and documentation, which were then analyzed using content analysis techniques. The findings show the existence of four aesthetic elements in the form of themes, shapes, colors, and motifs based on Herbert Read's aesthetic theory. There is a relevance between the aesthetic elements and the content of expressive drawing submaterial. First, the principle of balance is found with the four aesthetic elements that serve to obtain references. Secondly, the submaterial of analyzing and concluding the principle of balance serves as a maturation of the concept that has been formed in the initial exploration. Third, the practical activities function in realizing the four aesthetic elements in a work of art.